Extensive Diversification of Human Immunodeficiency Virus Type 1 Subtype B Strains during Dual Infection of a Chimpanzee That Progressed to AIDS - Wei, Qing (American Society for Microbiology, 1998)
A chimpanzee (C-499) infected for more than 9 years with two subtype B isolates of human immunodeficiency virus type 1 (HIV-1), one (HIV-1(SF2)) that replicates poorly and one (HIV-1(LAV-1b)) that replicates efficiently in chimpanzees, died of AIDS 11 years after initial infection (F. J. Novembre et al., J. Virol. 71:4086–4091, 1997). Nucleotide sequence and phylogenetic analyses of the C2 to V5 region of env (C2-V5(env)) in proviral DNA from peripheral blood lymphocytes obtained 22 months before death revealed two distinct virus populations. One of these populations appeared to be a recombinant in env, having the V3 loop from HIV-1(SF2) and the V4-V5 region from HIV-1(LAV-1b); the other population had evolved from HIV-1(LAV-1b). In addition to C2-V5(env), the entire p17(gag) and nef genes were sequenced; however, based on nucleotide sequences and phlyogeny, whether the progenitor of the p17(gag) and nef genes was SF2 or LAV-1b could not be determined. Compared to the two original viruses, the divergence of all clones of C2-V5(env) ranged from 9.37 to 20.2%, that of p17(gag) ranged from 3.11 to 9.29%, and that of nef ranged from 4.02 to 7.9%. In contrast, compared to the maximum variation of 20.2% in C2-V5(env) for C-499, the maximum diversities in C2-V5(env) in proviruses from two chimpanzees infected with HIV-1(LAV-1b) for 9 and 10 years were 9.65 and 2.48%, respectively. These results demonstrate that (i) two distinct HIV-1 populations can coexist and undergo extensive diversification in chimpanzees with progressive HIV-1-induced disease and (ii) recombination between two subtype B strains occurred even though the second strain was inoculated 15 months after the first one. Furthermore, evaluation of env genes from three chimpanzees infected with the same strain suggests that the magnitude of HIV-1 diversification could be related to higher viral burdens, manifestations of disease, and/or dual infection.